The Communist Party of Malaya: : From founding to decision to join peace talks - Abdulloh, Maylisa (Journal of Letters, 2023)
This article examines the Communist Party of Malaya (CPM) from its founding to the party's decision to join the peace talks in 1989. The article also presents and analyzes the consistencies and conflicts between information from CPM documents, books by former CPM leaders, books, academic articles, dissertations, and related research to understand the overall CPM movement including its controversies and limitations. The study found that there are some inconsistencies between the information in party documents, former CPM leaders and party members’ books and that recorded by some scholars and historians. Issues about the pre-war period need to be discussed, especially in relation to the founding of the party. During World War 2, the party played an important role in resisting the Japanese invasion of Malaya. After the war, the party was able to move openly, but also operated underground movements, including supporting protests and strikes, until it received greater support from the Chinese in Malaya. However, the movement led to the British government in Malaya declaring a state of emergency in 1948. The proclamation of the Malayan state of emergency is an issue that is examined in this study. It is possible that the CPM was used as a pretext by the British government to curb the resistance of Malay left groups. However, the party had to move its base into the deep jungle and use insurgency operations to fight against the British government. The British counterinsurgency forced the party to retreat to the Malaya-Thai border and it was decided to halt the movement in 1959. In 1961, the party decided to resume the battle and use the Malaya-Thai border area as a base, repeatedly but unsuccessfully attempting to send troops to Malaya. In 1989, the party joined peace talks with the Malaysian government using the Thai government as a mediator.